2021
DOI: 10.1002/ange.202015247
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Synthesis of Photoactive Polymers on a Living Cell Surface via Bio‐Palladium Catalysis for Modulating Biological Functions

Abstract: Cell surface engineering with functional polymers is an effective strategy to modulate cell activity. Here, a bio‐palladium catalyzed polymerization strategy was developed for in situ synthesis of conjugated polymers on living cell surfaces. Through Sonagashira polymerization, photoactive polyphenyleneethynylene (PPE) is synthesized on the cell surface via cell‐generated bio‐Pd catalyst. The in situ formed PPE is identified by excellent light‐harvest capacity and blue fluorescence on the surfaces of E. coli an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…From Qi et al, bio-palladium catalysts were found to synthesize photoactive polystyrene (PPE) on the surface of C. pyrenoidosa cells. It could expand light absorption and accelerate the cyclic electron transport, thus increasing the synthesis of ATP [38].…”
Section: Dye/polymer-microorganism Hybrid Systemmentioning
confidence: 99%
“…From Qi et al, bio-palladium catalysts were found to synthesize photoactive polystyrene (PPE) on the surface of C. pyrenoidosa cells. It could expand light absorption and accelerate the cyclic electron transport, thus increasing the synthesis of ATP [38].…”
Section: Dye/polymer-microorganism Hybrid Systemmentioning
confidence: 99%
“…In another work, bio-palladium catalyzed polymerization strategy for in situ synthesis of the conjugated polymers on living cell surfaces was applied to modify the cell surface (Figure 5C). 126 Specifically, photoactive polyphenyleneethynylene (PPE) polymer was employed in Sonagashira polymerization reaction being catalyzed by the in situ formed surface bio-Pd catalysts. The polymer formation process on cell surface could be easily traced due to the PPE blue fluorescence.…”
Section: Polymer-based Nanomaterialsmentioning
confidence: 99%
“…Nevertheless, modification usually requires a large excess of reactive polymers owing to low conjugation efficiency of polymers to cell surface caused by exogenous repulsion. To solve this key issue, Qi et al [55] . have taken a novel measure in constructing conjugated polymer‐based biohybrid system, by means of in‐situ polymerization strategy.…”
Section: Constructing Strategies For Whole‐cell‐based Pbssmentioning
confidence: 99%
“…have taken a novel measure in constructing conjugated polymer‐based biohybrid system, by means of in‐situ polymerization strategy. Considering the cell surface generally exists multiple Pd binding sites such as carboxyl, amino and phosphate groups, [56] the cell surface of C. pyrenoidosa could be modified with photoactive polyphenyleneethynylene (PPE) via Sonagashira polymerization catalyzed by the in‐situ formed surface bio‐Pd catalysts [55] . The in‐situ synthesized light‐harvesting polymer PPE regulated the electron‐transport pathways and led to an elevated cyclic electron transport and enhanced activity of PSI for producing more ATP (Figure 7c).…”
Section: Constructing Strategies For Whole‐cell‐based Pbssmentioning
confidence: 99%